Electrochemical activation of sulfate by BDD anode in basic medium for efficient removal of organic pollutants. (November 2018) - Chen, Luchuan; Lei, Chaojun; Li, Zhongjian; Yang, Bin; Zhang, Xingwang; Lei, Lecheng
Abstract: Electrochemical advanced oxidation processes (EAOPs) based on hydroxyl radicals ( OH) have some limitations when they are applied to real wastewater treatment, such like strict requirements on pH (acidic electrolyte) and high energy consumption. Compared to OH, Sulfate radicals (SO4 – ) have high redox potential in wider range of pH (2–9). In this study, SO4 – were efficiently produced by electrochemical activation of SO4 2− at boron doped diamond (BDD) anode. The degradation rate of 2, 4-DCP (k = 0.828 ± 0.05 h −1 ) in the presence of Na2 SO4 was approximately 4 times than that without Na2 SO4 (k = 0.219 ± 0.01 h −1 ), indicating that SO4 – exhibited higher reactivity than OH at initial pH = 9. Moreover, the amount of O2 decreased by 65% after 100 min during electro-oxidation of 2, 4-DCP and the specific energy consumption per unit TOC (ECTOC ) was reduced by 70% when the concentration of Na2 SO4 increased from 0.01 to 0.1 M. The impact of sulfate ions in the electrochemical advanced oxidation were investigated. Electron spin resonance (ESR) measurements were conducted to identify the formation of SO4 – . Electrolysis of 2, 4-DCP with specific radical scavengers (ethanol and tert-Butanol) were conducted and the results revealed that SO4 – were mainly produced by one-electron loss of sulfate at basic condition. Electro-generation persulfate was measured and participation of non-radical activation of persulfate was investigated. O2 production was quantified and we found electrochemical activation of sulfate could inhibit water dissociation. Taken all findings, a mechanism of electrochemical activation of sulfate at BDD anode was summarized. This technology eliminates the requirement for pH adjustment for wastewater treatment and makes EAOPs more effective and economic as well. Graphical abstract: Image 1 Highlights: 2, 4-dichlorophonel (2, 4-DCP) degradation is significantly improved at basic condition. Sulfate radicals and their main formation path are discussed. Participation of non-radical activation of persulfate and water dissociation is investigated. A proposal mechanism of electrochemical activation of sulfate at BDD anode is summarized.